Role of Foreign Manufacturing Companies in Komárom-esztergom County’s Economy - Peredy, Zoltán; Péli, László (Acta Carolus Robertus, 2024)
In the past three decades, due to favorable conditions and profit opportunities Komárom-Esztergom County (KEM) has become the preferred region for the first, second and third round of investment decisions in Eastern and Central Europe for capacity building, expansion and technological modernization of large multinational companies (MNE’s) operating in various segments of the manufacturing industry. In the framework of a broader research, which aiming a broader regional analysis of the KEM manufacturing industry, in this study the authors analyze the impacts the gross value added (GVA) produced by the local units of MNE’s and their employed local workforce on the KEM economy. Furthermore, they make comparison between productivity of MNE’s local units compares to the average productivity of the county. In addition, they also address whether the economic growth and development generated by these manufacturing investments are temporary or permanent, i.e. whether the center-periphery development trap situation that is usually characteristic of manufacturing counties in KEM can be avoided. Due to the high GVA ratio, low value-added activities and low productivity of the manufacturing regions, the economic growth and development generated by MNE’s investments is temporary and a decline is expected in the future, which will also hold back the country's development. How to avoid this trap situation in KEM, to make the dynamic, sustainable economic development that started in the past and what economic strategic change of direction is necessary for this.
Keywords: Komárom-Esztergom county; manufacturing industry; gross value added; productivity; catching-up